Team Handball World Cup Championship 2013 - Analysis Study - Hassan, A. (Journal of Human Sport & Exercise, 2014)
The world cup of men`s handball team championships was analysed using data from all matches in order to determine tactical differences at the elite level. The first aim of this study was to conduct a technical analysis of current handball and to determine factors related to success in this sport discipline. The second aim was to compare the data of first eight teams with other next teams.An analysis of the performance of the participating teams` video tapes and CD`s, in the collection of matches, was completed on all the teams taking part in the World Cup Handball Championship 2013. . This technical analysis also used cumulative statistics from the International Handball Federation. There were 24 teams in this competition , these were classified participating 2013 into three groups according to the final classification of the winning teams. Variables were identified relating to results of matches (win or lose), and data collection of games was completed by selecting certain codes for each variable of the study variables.The variables included:- Total shots, Total successful shots, Breakthroughs, Breakthroughs successful, Fast break successful, Fast breaks, Red C, Yellow C, 2Min, Steal, Blocked, Assist, Tech. Faults, 6M shots, 6M successful shots, Wing shots, Wing successful shots, 9M shots, 9M successful shots, 7M shots, 7M successful shots.The technical variables used to compare the teams included: the average number of shots, the efficiency of shots, the efficiency of breakthroughs, fast break goals per team, the efficiency of fast breaks, the average number of 7M shots, the efficiency of 7M shots, the average number of 6M shots, the efficiency of 6M shots, the average number of 9M shots, the efficiency of 9M shots, the average number of wing shots, the efficiency of wing shots, offence (The average number of tech faults, the efficiency of tech faults, the average number of assist, the efficiency of assist), defense ( The average number of blocked, the efficiency of the average number of steals, the efficiency of steals), and penalties (2M, yellow card, red card).This technical analysis used cumulative statistics from the International Handball Federation. ANOVA revealed significant differences between the first eight teams in the World cup championships 2013 and their counterparts in the other two groups (group two, teams from 9-16 and group three, teams from 17-24) in terms of several technical variables. The results showed that the above various affected the ranking in favor of the world cup teams in significant international teams.